ANALISIS PENCEMARAN AIR SUNGAI JOMPI KABUPATEN MUNA SEBAGAI SUMBER AIR BAKU PDAM KOTA RAHA - Laode Sabaruddin; La Ode Midi; Isne Walsukni (Jurnal Ecogreen, 2019)
The purpose of this study was to determine the Water Pollution Index of the Jompi River in Muna Regency as Raw Water for PDAM Kota Raha. This research was carried out in April to May 2018, using the Pollution Index Analysis method carried out with reference to the Regulation of the Minister of Environment No. 115 of 2003 concerning Guidelines on the Status of Water Quality. with physical parameters (odor, color, turbidity, taste, dissolved solids (TDS) and suspended solids (TSS)), organic chemical parameters (oil and fat, surfactants / detergents), biological parameters (total Coliform and number of Escherichia coli) . Still in the classification meets quality standards. While the average percentage of the River Jompi Pollution Index has a classification of ≤1, which means that the River Jompi is still in good condition.